2005
DOI: 10.1191/1352458505ms1210oa
|View full text |Cite
|
Sign up to set email alerts
|

A randomized blinded trial of combination therapy with cyclophosphamide in patients with active multiple sclerosis on interferon beta

Abstract: Combination therapy with CY/MP and IFNbeta-Ia decreased the number of Gd+ lesions and slowed clinical activity in patients with previously active disease on IFNbeta alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 37 publications
1
28
1
1
Order By: Relevance
“…We observed that over 50% of patients with over 1 year of follow-up after the cessation of therapy continued to experience frequent relapses and required additional second-line treatments, suggesting that cyclophosphamide treatment did not induce a permanent suppression of the inflammatory process in this cohort of pediatric MS patients. Our results may differ from observations in adults 1 because of the selection of a particularly active pediatric MS population, or may be due to key differences in the immunologic response in children compared to adults, a hypothesis which requires further exploration.…”
Section: Figure Clinical Scores Precyclophosphamide and Postcyclophoscontrasting
confidence: 56%
See 1 more Smart Citation
“…We observed that over 50% of patients with over 1 year of follow-up after the cessation of therapy continued to experience frequent relapses and required additional second-line treatments, suggesting that cyclophosphamide treatment did not induce a permanent suppression of the inflammatory process in this cohort of pediatric MS patients. Our results may differ from observations in adults 1 because of the selection of a particularly active pediatric MS population, or may be due to key differences in the immunologic response in children compared to adults, a hypothesis which requires further exploration.…”
Section: Figure Clinical Scores Precyclophosphamide and Postcyclophoscontrasting
confidence: 56%
“…It is generally administered as monthly maintenance therapy, in some cases preceded by an induction course. Cyclophosphamide has been shown to be effective in relapse rate reduction 1,2 and in control of MRI lesion accrual 1,3 ; however, effects in delaying disease progression have been variable. [4][5][6][7] Several studies have suggested that cyclophosphamide treatment may be most beneficial in younger adult patients, [7][8][9] and in patients with early secondary progressive MS. 6,7,10 MS onset before the age of 18 years is estimated at 2.7%-10.5% [11][12][13] of all patients.…”
mentioning
confidence: 99%
“…Although well-designed trials have failed to conclusively demonstrate the efficacy of cyclophosphamide monotherapy, it is possible that combining cyclophosphamide, IFNb, and other agents may be an option for patients failing previous therapy and with limited treatment options. Data from a randomized, single-blinded, placebo-controlled, multicenter trial combining monthly cyclophosphamide and corticosteroids with IFNb indicate that this combination has some efficacy in reducing clinical relapses and MRI lesions [Smith et al 2005].…”
Section: Cyclophosphamidementioning
confidence: 99%
“…Cyclophosphamide is typically infused monthly (with or without induction) and works as an immunosuppressing agent affecting cytokine expression (with pronounced effects on IL-12) along with T-cell and B-cell function [95]. In adults with RRMS, cyclophosphamide appears to reduce relapse rate and the accrual of new lesions on MRI [96,97] Fig. 2 Proposed algorithm for the approach to treating a pediatric patient with multiple sclerosis (MS) [40].…”
Section: Cyclophosphamidementioning
confidence: 99%